Historical relationship of the honeybee (Apis Mellifera) and its forage; and the current state of beekeeping within South Africa - Hutton-Squire, James Peter (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScConsEcol)--Stellenbosch University, 2014.